Simulation of laminar and turbulent concentric pipe flows with the isogeometric variational multiscale method - Ghaffari Motlagh, Y.; Ahn, H.; Hughes, T.; Calo, Victor (2013)
We present an application of the residual-based variational multiscale modeling methodology to the computation of laminar and turbulent concentric annular pipe flows. Isogeometric analysis is utilized for higher-order approximation of the solution using Non-Uniform Rational B-Splines (NURBS). The ability of NURBS to exactly represent curved geometries makes NURBS-based isogeometric analysis attractive for the application to the flow through annular channels. We demonstrate the applicability of the methodology to both laminar and turbulent flow regimes. © 2012 Elsevier Ltd.